Constitutional structures of parliamentary government in case of Germany and RA - Kalantaryan, Edgar (YSU Journal of International Affairs, 2021)
The choice of an effective government form is one of the most important issues facing a state that has embarked on the path of democratic development. A comprehensive study of the issues, like mechanism of parliamentary formation, mixed and proportional-majority electoral systems within the framework of parliamentary government model deserves special attention. In this case, the example of the leading countries, particularly Germany is essential that have created a stable basis for the development of the country. Germany's successful experience can be useful also for the Republic of Armenia (RA), which has adopted a new parliamentary form of government. The study of foreign experience can contribute to the development and enhancement of the role of parliament in the RA.
Keywords: Parliament; distribution of mandates; parliamentary government; constitutional amendments; proportional electoral system; voting; effective governance; legislature